Determination of Sex from Hyoid bone – Is it Feasible? - James, R I; Bakkannava, r S; Anitha, S (Journal of Indian Academy of Forensic Medicine, 2022)
Identifying an individual is a priority from womb to tomb. Historically, human identification is one of the most challenging subjects that man has confronted. Alves identity is a set of physical characteristics, functional or psychic, normal or pathological, that defines an individual. Among various parameters of human identification, sex determination is an important first step in the development of a biological profile, as methods to estimate other components of the profile depend on sex. Sex determination is one of the key questions addressed when formulating this profile – its knowledge immediately eliminates 50% of the population from the process of identification. In this study we took seven linear measurements of hyoid bone to determine the sex. Among the seven linear measurements Total Hyoid Length (THL) and Body Length (BL) were considered to be significant in predicting the sex of the individual (’p’ value < 0.05). The discriminant equation derived gives an accuracy of 62 % and the measure of agreement of Kappa between the cut-off value derived from the equation and actual sex was 0.24 (Statistically insignificant).